Digital Literacy Competence Levels of Indonesian Junior High School Students Based on Activities Through The 5m Approach - Andi Mursidi; Buyung Buyung; Eka Murdani (STKIP Singkawang, 2022)
Students’ competence to utilize digital technology to access information as learning sources has become a necessity as experienced during the covid-19 pandemic. Students should have the digital literacy competence to support the students’ learning processes. This research was conducted to reveal the digital competence levels covering internet searching, hypertextual navigation, content evaluation, and knowledge assembly based on activities made by the students of Junior High Schools in Singkawang. The samples were selected using a proportional random sampling technique and 75 respondents were selected representing the students of Junior High Schools in Singkawang. The collected data were then processed using a descriptive statistical analysis with a quantitative approach. The statistical test was conducted using mini-step Program with Rasch modeling to measure the students’ digital literacy competence levels at Junior High Schools in Singkawang. The research results showed that the digital literacy competence level test measuring instrument was considered valid and reliable. The digital literacy competence level with high logit value of +3.78 logit also showed high problem-solving competence level. The students’ digital literacy competence level based on activities was classified into high category. Meanwhile, the activities made by the students included 5M: searching and selecting information (M1), managing information (M2), analyzing information (M3), utilizing information (M4), and sharing information (M5).